Pengaruh Peer Group Discussion Terhadap Peningkatan Pengetahuan Dan Sikap Remaja Tentang Pencegahan Perilaku Seks Bebas Remaja Usia 12-15 Tahun Di SMPN 2 Bangkinang Kota - Ariani, Fitri; Pattimura, Nastain Abubakar (JURNAL PENDIDIKAN KESEHATAN, 2024)
Adolescence is a transitional period from childhood to adulthood. Lack of knowledge among adolescents about the prevention of free sexual behavior from an early age can increase free sexual behavior during their growth and development. The purpose of this study is to determine the effect of peer group discussion on increasing knowledge and attitudes of adolescents about the prevention of free sexual behavior among adolescents aged 12-15 years at SMPN 2 Bangkinang Kota, class VIII. The sample of this study consisted of 22 students. The sampling technique used was simple random sampling. Data collection was done using a questionnaire. Data analysis in this study included univariate and bivariate analysis. The results of the study on the effect of peer group discussion on the knowledge and attitudes of adolescents about the prevention of free sexual behavior before the intervention (Pv= 0.000; Pv= 0.002 ? 0.05). It is hoped that respondents will seek information about the prevention of free sexual behavior from various sources, one of which is by using the peer group discussion method.